Design and build Virtual tour panorama 360 Hospitality Center UNP as promotional media - Dewi, Ika Parma; Prasetyo, Agung; Giatman, Muhammad; Wakhinuddin, Wakhinuddin; Samala, Agariadne Dwinggo (Politeknik Ganesha Medan, 2021)
The UNP Hospitality Center virtual tour application aims to help promote to potential visitors, and as an interactive promotional media. Hospitality Center UNP is an inn located in the Padang State University area and has various types of rooms and meeting facilities. Based on interviews with the UNP Hospitality Center internal parties, the promotions used are still using brochures. This tool only provides a little information to potential visitors about the rooms and facilities, namely only with photos and writing, this makes limited information that can be conveyed because with a brochure prospective visitors can only see one picture of each existing facility. The data collection stage was carried out by the method of interviews and direct observation. The next stage for developing the author's application uses the Multimedia Development Life Cycle (MLDC) method. consists of Concept, Design, Material Collecting, Assembly, Testing, and Distribution. The main features of this application are: hospitality profile, panorama list, location, floorplan and usage information. With these main features, it is found that by using the UNP Hospitality Center virtual tour application, it can make it easier to promote to prospective UNP Hospitality Center guests.